2021
DOI: 10.1364/oe.419009
|View full text |Cite
|
Sign up to set email alerts
|

Quantum-dot semiconductor lasers with prominent relative intensity noise and spectral characteristics

Abstract: Relative intensity noise (RIN) behavior of a quantum dot laser (QDL) at free running and under optical injection locking (OIL) has been reported in detail. Considering the mutual effects of the inhomogeneous and homogeneous broadenings, different and also non-routine RIN characteristics of a QDL at low, intermediate, and high homogeneous broadening regimes have been discussed. Results demonstrate that an injection-locked quantum dot laser exhibit enhanced characteristic over free-running operation along with l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The carrier and photon rate equations including Langevin noise sources can be described as follows: V is the volume, q is the charge, Γ is the confinement factor and vg is the group velocity. (16) Nonlinear-gain in Exs and Grs is given as…”
Section: Theoretical Model Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…The carrier and photon rate equations including Langevin noise sources can be described as follows: V is the volume, q is the charge, Γ is the confinement factor and vg is the group velocity. (16) Nonlinear-gain in Exs and Grs is given as…”
Section: Theoretical Model Descriptionmentioning
confidence: 99%
“…al reported that carrier noise originated from excited state and ground state of Q-Dot lasers increase the RIN of Q-Dot lasers, whereas enhancing energy difference between the ground state and the excited state reduce carrier noise contribution from the excited state [15]. As a result, there have been some papers investigating RIN of Q-Dot lasers for InGaAs-GaAs and InAs-InP [9][10][11][13][14][15][16][17][18][19][20][21]. However, most of them are not enough to clearly explain the RIN spectrum of Q-Dot lasers.…”
Section: Introductionmentioning
confidence: 99%
“…The carrier and photon rate equations including Langevin noise sources can be described as follows: V is the volume, q is the charge, Γ is the confinement factor and vg is the group velocity. (16) Nonlinear-gain in Exs and Grs is given as…”
Section: Theoretical Model Descriptionmentioning
confidence: 99%
“…al reported that carrier noise originated from excited state and ground state of Q-Dot lasers increase the RIN of Q-Dot lasers, whereas enhancing energy difference between the ground state and the excited state reduce carrier noise contribution from the excited state [15]. As a result, there have been some papers investigating RIN of Q-Dot lasers for InGaAs-GaAs and InAs-InP [9][10][11][13][14][15][16][17][18][19][20][21]. However, most of them are not enough to clearly explain the RIN spectrum of Q-Dot lasers.…”
Section: Introductionmentioning
confidence: 99%